“Nilai-nilai Bawah Tanah:” Tinjauan Antropologis Tentang Anarkisme Dalam Paradigma Cultural Studies di Kalangan Anak Muda Kota Makassar - Fajri, Muhammad Faris Al (Emik, 2024)
The anarchist punk subculture started with a spirit of resistance, but unfortunately the popular culture that absorbed this subculture has caused it to lose its resistance essence. Despite its spirit, the subculture has been integrated into the very system it previously resisted. This article focuses on the ways in which young people in Makassar City consume "underground values" and their anarchic forms of expression in adopting these values through creativity, especially in the form of music. This research uses Critical Ethnography as a cultural research approach that uses a critical paradigm, which criticizes and offers solutions to cultural injustice, marginalization, exploitation, and subordination. The Cultural Studies paradigm highlights conflicts, interests, and power in culture. The informants in this article are young people who join a group that consumes "underground values" on a daily basis. The data collection techniques used in this research are through interviews and participatory observation used in the context of qualitative research because it allows researchers to directly observe the actions, attitudes, and atmosphere that exist. The informants in this study were determined by purposive sampling with reference to the following criteria: Young people who join subcultures that consume “subteterranean value” and express them in their daily lives. The results show that political norms and culture influence individual experiences, even encouraging adaptation to expectations that may conflict with personal desires. The transformation of subcultures and "underground values" that originally focused on resistance to the dominant culture, but later integrated into the structure of the dominant culture. The influence of the dominant culture creates alienation and inequality, limiting the freedom of individuals to shape their identity. "Underground values" are a form of alternative and counterculture to the dominant culture, reflecting strong values of collectivism and anti-hierarchy. Despite the transformation, the essence of underground values continues to criticize capitalism and conventional norms in society. This subculture continues to offer a space for expression, despite the pressures and changes that occur over time.